HAC1 and HAF1 Histone Acetyltransferases Have Different Roles in UV-B Responses in Arabidopsis - Fina, Julieta P.; Masotti, Fiorella; Rius, Sebastián P.; Crevacuore, Franco; Casati, Paula (Frontiers in Plant Science, 2017)
Arabidopsis has 12 histone acetyltransferases grouped in 4 families: the GNAT/HAG, the MYST/HAM, the p300/CBP/HAC and the TAFII250/HAF families. We previously showed that ham1 and ham2 mutants accumulated higher damaged DNA after UV-B exposure than WT plants. In contrast, hag3 RNA interference transgenic plants showed less DNA damage and lower inhibition of plant growth by UV-B, and increased levels of UV-B-absorbing compounds. These results demonstrated that HAM1, HAM2 and HAG3 participate in UV-B-induced DNA damage repair and signaling. In this work, to further explore the role of histone acetylation in UV-B responses, a putative function of other acetyltransferases of the HAC and the HAF families was analyzed. Neither HAC nor HAF acetyltrasferases participate in DNA damage and repair after UV-B radiation in Arabidopsis. Despite this, haf1 mutants presented lower inhibition of leaf and root growth by UV-B, with altered expression of E2F transcription factors. On the other hand, hac1 plants showed a delay in flowering time after UV-B exposure and changes in FLC and SOC1 expression patterns. Our data indicate that HAC1 and HAF1 have crucial roles for in UV-B signaling, confirming that, directly or indirectly, both enzymes also have a role in UV-B responses.